Vitamin D receptor gene polymorphisms (TaqI and ApaI) in relation to 25-hydroxyvitamin D levels and coronary artery disease incidence - Abu El Maaty, Mohamed A.; Hassanein, Sally I.; Sleem, Hameis M.; Gad, Mohamed Z. (Journal of receptors and signal transduction, 2015)
Context/objective: Previous studies have illustrated the association of the ApaI and TaqI polymorphisms of the vitamin D receptor gene, located in non-coding and coding regions, respectively, with diseases such as cancer and cardiovascular disease; however, investigating such association in Egyptian patients with coronary artery disease (CAD) has never been formerly attempted. Materials and methods: Male patients (n = 137), 35-50 years of age, with verified CAD, were recruited alongside age- and sex-matched controls (n = 58). Genotyping and 25-hydroxyvitamin D [25(OH)D] measurement were performed by polymerase chain reaction RFLP and HPLC, respectively. Results: Comparison of the genotypic distribution of both the TaqI and ApaI polymorphisms between patients and controls yielded insignificant results (p = 0.55 and 0.7, respectively). Comparison of the allelic distribution of both polymorphisms also yielded insignificant results. The TaqI polymorphism was not found to predict 25(OH)D levels, whereas the wild-type genotype of the ApaI polymorphism was associated with greater levels of 25(OH)D (p = 0.02), taking all subjects into consideration. Discussion/conclusion: This study presents the ApaI and TaqI polymorphisms as non-influencing players in the pathogenesis of CAD in Egyptian males and the ability of only the ApaI polymorphism to predict 25(OH)D levels, thus warranting further investigations of the triangular relationship between the polymorphisms, 25(OH)D and CAD incidence.